2015
DOI: 10.1007/s11523-015-0386-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Targeting of Bladder Tumor Growth, Survival, and Epithelial-to-Mesenchymal Transition with a Novel Therapeutic Combination of Acetazolamide (AZ) and Sulforaphane (SFN)

Abstract: We suggest that reductions in these components could be linked with downregulation of the survival mediated Akt pathway and suggested an active role of the Akt pathway in bladder cancer. Altogether, our in vitro and pre-clinical model data support the potential use of an AZ + SFN combination for the treatment of bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 52 publications
3
56
0
Order By: Relevance
“…Furthermore, PD98059, a specific inhibitor of MEK, the upstream activator protein of ERK1/2, remarkably suppressed the enhanced invasion and migration abilities of UBC cells induced by CCL21. Based on these results, we came to a conclusion that the PI3K/AKT and ERK pathways play a critical role in the carcinogenesis and progression of UBC (78,8183), but the ERK pathway may play a more important role in the CCL21/CCR7-induced progression of UBC than the AKT pathway.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, PD98059, a specific inhibitor of MEK, the upstream activator protein of ERK1/2, remarkably suppressed the enhanced invasion and migration abilities of UBC cells induced by CCL21. Based on these results, we came to a conclusion that the PI3K/AKT and ERK pathways play a critical role in the carcinogenesis and progression of UBC (78,8183), but the ERK pathway may play a more important role in the CCL21/CCR7-induced progression of UBC than the AKT pathway.…”
Section: Discussionmentioning
confidence: 95%
“…However, this expectation was foiled since application of SFN caused diminished p27 expression in both everolimus-sensitive and -resistant tumor cells. Other investigators have reported that applying SFN to several tumor cell lines (but not to RCC cells) leads to p27 induction [32, 33]. Another investigator found no modification of p27 by SFN [34].…”
Section: Discussionmentioning
confidence: 99%
“…Pathways involved in the induction and sustaining of cancer that can be targeted include autocrine growth factors, hypoxia, carbonic anhydrase, antioxidant response, apoptosis, angiogenesis and epigenetic factors. These pathways have strong implications in cancer, and our current investigations, in particular, have further supported their roles in tumorigenesis [15, 28, 31]. Here, we provide an updated clinical review of the most current repurposed and prospective therapeutic combination treatments that target these pathways.…”
Section: Introductionmentioning
confidence: 96%